The Effect of Canva-Based Learning Media on Improving Students’ Learning Outcomes in Islamic Religious Education Subjects - Febriansyah Putra; Parlaungan Lubis; Nurhaizan Sembiring (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
This study was motivated by the importance of innovative learning media in improving students’ learning outcomes in Islamic Religious Education. Learning processes that are still predominantly based on conventional methods often limit students’ active engagement, resulting in suboptimal learning achievement. Therefore, this study aimed to analyze the effect of Canva-based learning media on the learning outcomes of eleventh-grade students at Broadcasting Bina Creative (BBC) Vocational High School, Medan. The study employed a quantitative approach with a correlational research design. The population consisted of all eleventh-grade students, while the sample comprised 30 students selected using a predetermined sampling technique. Data were collected through questionnaires and documentation and were analyzed using validity, reliability, classical assumption, t-test, and coefficient of determination analyses with the assistance of IBM SPSS Statistics 25. The findings revealed that Canva-based learning media had a positive and significant effect on students’ learning outcomes, as indicated by a t-test significance value of 0.008 (< 0.05). Furthermore, the coefficient of determination (R Square) value of 0.585 indicated that Canva contributed 58.5% to the improvement of students’ learning outcomes, while the remaining 41.5% was influenced by other factors. These findings confirm that Canva is an effective digital learning medium for enhancing the quality of Islamic Religious Education learning.